Unjuk Kerja Vaccine Covid-19 Carrier Box Menggunakan Thermoelectric Cooler Dan Heat Pipe Pada Variasi Pembebanan Dan Variasi Input Tegangan - Sitompul, Nathaniel Andrew Sahala; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The vaccination program is targeted to last until March 2022. Based on vaccination targets, the widely used vaccine is a vaccine with a distribution temperature of 2-8 ° C of 276.5 million. The thing that really needs to be observed is how to distribute the covid-19 vaccine from one place to another that is able to keep the temperature so that the vaccine can be maintained and not damaged before vaccination. From this problem one solution to distribute the covid-19 vaccine at a distribution temperature of 2-8 ° C with a cooling box using an environmentally friendly cooling system and has low power, one of which is adding Heat pipe and Thermoelectric Cooler, which can maintain the temperature of the vaccine. Heat pipe used by cooper as heat absorption, while in Thermoelectric Cooler type TEC2-25408 which can later maintain the temperature of the distribution of the covid-19 vaccine 2-8 ° C. Based on the calculation of the highest COP is 0.354. After testing, the Vaccine Covid-19 Carrier Box with Thermoelectric Cooler and Heat pipe that is run can maintain the vaccine temperature of 2-8 °C.Keywords : Vaccine covid-19 carrier box, thermoelectric cooler, heat pipe, coefficient of performace (COP)